2022
DOI: 10.1186/s12884-021-04338-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of preconception care improvement scale (PCIS) in a resource-limited setting

Abstract: Background Preconception care helps to close the gaps in a continuum of care. It is of paramount importance to reduce maternal and child adverse pregnancy outcomes, increase the utilization of services such as antenatal care, skilled delivery care, and post-natal care, and improve the lives of future generations. Therefore, a validated instrument is required. The purpose of this study was to develop and validate the preconception care improvement scale (PCIS) in a resource-limited setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(52 reference statements)
0
3
0
2
Order By: Relevance
“…The Charter's emphasis on the preconception period represents a crucial contribution to this discourse. It resonates with recent calls for a life-course approach to health, emphasising the role of preconception conditions in determining future health outcomes (Hall et al, 2023;Pentecost & Meloni, 2020;Stephenson et al, 2018;Teshome et al, 2022;World Health Organization, 2014).…”
Section: N T Er Nationa L R Igh Ts Fr a M Ewor K S: T H E G A Pmentioning
confidence: 79%
“…The Charter's emphasis on the preconception period represents a crucial contribution to this discourse. It resonates with recent calls for a life-course approach to health, emphasising the role of preconception conditions in determining future health outcomes (Hall et al, 2023;Pentecost & Meloni, 2020;Stephenson et al, 2018;Teshome et al, 2022;World Health Organization, 2014).…”
Section: N T Er Nationa L R Igh Ts Fr a M Ewor K S: T H E G A Pmentioning
confidence: 79%
“…En la Tabla 4 se puede observar que para las intenciones de emprendimiento e identificación de oportunidades, el valor del estadístico alfa de Cronbach en las escalas utilizadas para las variables es fiable y consistente que, como explican Loch et al (2021) y Teshome et al (2022), se encuentra en el rango correcto (0,7 -0,9) con una consistencia casi perfecta.…”
Section: Resultados Y Discusiónunclassified
“…Estos resultados concuerdan con otros que consideran el reconocimiento de oportunidades como un antecedente para predecir la intención emprendedora (Puni et al, 2018), mientras que algunos académicos lo han mostrado como el sucesor del proceso de intención emprendedora (Asante y Affum-Ossei, 2019;Jarvis, 2016), aunque hay poca literatura disponible en el medio ecuatoriano sobre la identificación de oportunidades y la relación de intenciones de emprendimiento. Por otra parte, los niveles altos o bajos que puedan darse también se ven influenciados por el tamaño de la muestra que se utilice porque, como lo expresan Teshome et al (2022), el alfa de Cronbach tiende a ser menos fiable (valor < 0.7) cuando el tamaño de la muestra es muy pequeño.…”
Section: Resultados Y Discusiónunclassified
“…PC is a subject that may be learned through education or experience. According to studies, women who receive prenatal care are more informed and frequently manifest risk-reducing behaviors [ 6 , 7 ]. Women who receive prenatal care also use folic acid more often throughout the advised time frame.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that women who receive PC interventions are more knowledgeable about prevention strategies, and even brief counselling can increase their understanding of both general and specific preconception health concerns. Murphy et al indicated that PC is linked to better pregnancy management and a lower chance of negative pregnancy results [ 7 ]. Dorney et al reported that GPs could significantly increase both men’s and women’s access to preconception health counselling and evaluation services [ 8 ].…”
Section: Introductionmentioning
confidence: 99%